2003
DOI: 10.1177/13634615030402006
|View full text |Cite
|
Sign up to set email alerts
|

Jungians and the Rise of Psychotherapy in Japan: A Brief Historical Note

Abstract: Scholars of transcultural psychiatry have long wondered why psychoanalysis has remained marginal in Japan, despite its early introduction there. Psychotherapy, however, has been steadily growing in popularity, and Jungians have played no small part in this development. This article provides a brief historical sketch of psychotherapy in Japan by focusing on how Jungians have cultivated a following through imaginative cultural critiques and therapeutic practices such as sandplay therapy. The article also touches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…4 On psychoanalytic influences in Dutch-occupied Java and other regions in the Indonesian archipelago, see Gouda (2009). 5 For discussions of transcultural psychiatry in other parts of East Asia, see, for example, Kitanaka (2003); Suh (2013). 6 See the essays in Anderson et al (2011);Damousi and Plotkin (2012); ffytche and Pick (2016).…”
Section: Endnotesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 On psychoanalytic influences in Dutch-occupied Java and other regions in the Indonesian archipelago, see Gouda (2009). 5 For discussions of transcultural psychiatry in other parts of East Asia, see, for example, Kitanaka (2003); Suh (2013). 6 See the essays in Anderson et al (2011);Damousi and Plotkin (2012); ffytche and Pick (2016).…”
Section: Endnotesmentioning
confidence: 99%
“…For discussions of transcultural psychiatry in other parts of East Asia, see, for example, Kitanaka (2003); Suh (2013). …”
mentioning
confidence: 99%
“…Sandplay therapy has become a widely used form of treatment in Japan, due to the protective free space and playful self-discovery it provides (Kitanaka, 2003). Prior research has indicated that the families of immigrant preschoolers who have experienced adversity before migration can benefit from creative expressive workshops such as sandplay (Rousseau, Benoit, Lacroix, & Gauthier, 2009).…”
Section: Sandplay In Response To the World Trade Center (Wtc) Attacksmentioning
confidence: 99%